aCIOSm4: An Asynchronous CIOS Algorithm - Liang, Yuqing; Wang, Yan; Zhang, Haoshan; He, Anping (2020 IEEE 5th International Conference on Integrated Circuits and Microsystems (ICICM), 2020)
This article proposes a novel asynchronous CIOS algorithm and its asynchronous architecture that can accelerate the encryption and decryption of RSA cryptosystem without increasing area. This algorithm merges two loops of the classical CIOS algorithm with the following advantages: reducing the number of operations by half, decreasing the complexity of hardware implementation by facilitation of the asynchronous pipelined parallel calculation, and saving the resources. Experimental results show that the average calculation time of our algorithm is only 9.8us, which is 36.5% faster than the classical one. In addition, our algorithm is also embedded in an asynchronous 1024-bits RSA cryptographic circuit, compared with the CIOS algorithm, the encryption and decryption speed are increased by 37.5%.